IMPROVED QUALITY MANAGEMENT OF LEARNING: In MTs Negeri Model Cigugur Kuningan - Hary Priatna Sanusi (Jurnal Isema : Islamic Educational Management, 2016)
The most urgent demands in the development of quality education and relevant to the needs of the community is increased capacity. School principals should be able to give birth to innovative ideas that are useful for generating policy alternatives in building. The education system is an efficient, high quality and in accordance with the needs of society in various fields of life. Effectiveness of management functions in learning activities with the application of the principles of lesson planning, organizing functions in learning, actuating functions in learning, and monitoring functions in learning activities. Learning management application that includes lesson planning, organizing learning, learning implementation, monitoring/ assessment of learning. Learning management can be seen from the number of new students who are always growing, produce learners who excel both in academic and non academic.